English Students’ Difficulties and Strategies in Comprehending Journal Articles - Panggabean, Amalda Syahraemy; Mahdum; Daud, Afrianto (PROJECT (Professional Journal of English Education), 2026)
This research explores the difficulties and the strategies faced by second-year students of the English Study Program at FKIP Universitas Riau in comprehending English journal articles. A descriptive quantitative approach was employed in this study, utilizing a sample of 77 fourth-semester students chosen through cluster random sampling. Data was collected through a questionnaire using a four-point Likert scale, designed to measure two variables: students' difficulties and strategies in comprehending journal articles. The results indicate that the main difficulties experienced by students include inability to use effective reading strategies, limited academic vocabulary, and lack of familiarity with the journal article format. Meanwhile, the strategy most used by students is Problem-Solving Strategies (PROB), followed by Global Reading Strategies (GLOB), and Support Strategies (SUP). These findings highlight that improving students’ mastery of academic vocabulary, familiarity with journal structures, and strategic reading skills is essential to enhancing their comprehension of academic texts.